2009
DOI: 10.2334/josnusd.51.635
|View full text |Cite
|
Sign up to set email alerts
|

Associations among distributions of dental postgraduate residents, dentists and clinical training facilities in Japan

Abstract: The purpose of this study was to evaluate the correlation and distribution of dental postgraduate residents, dentists and clinical training facilities in each prefecture to analyze the regional distribution and supply of dentists in Japan. The results were also compared with referential data for medicine. The coefficient of correlation between the dentist index and dental postgraduate resident index was r = 0.76 (P < 0.001) in 2006. The distribution (coefficient of variation) was greatest for the dental postgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Because Japan implemented mandatory vocational training for dentists (so-called junior resident year) in 2006, the new-entry dentists need to receive one-year postgraduate clinical training before they can practice freely anywhere or become the owner of a dental clinic in Japan. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…Because Japan implemented mandatory vocational training for dentists (so-called junior resident year) in 2006, the new-entry dentists need to receive one-year postgraduate clinical training before they can practice freely anywhere or become the owner of a dental clinic in Japan. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported on the regional distribution of dentists and physicians, university dental schools, medical schools, and postgraduate residents (10) . In this study, with respect to the current status of the regional distribution of dentists, we compare the number of dental hygienists against that of physicians and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the global standards proposed by the World Federation for Medical Education (1,2). Cross-sectional studies for each period have been reported regarding education at the pre-graduate clinical practical training and post-graduate clinical training levels (3)(4)(5)(6)(7)(8)(9). However, no studies on a clinical competency examination as an overall evaluation at the end of pregraduate clinical practical training and at the end of OSCAT as a pilot study with the objective of establishing a clinical competency evaluation for professionalism in dental education.…”
Section: Introductionmentioning
confidence: 99%